ПОЭТИКА ЛЮБВИ ШЕКСПИРА И НАВОИ В СРАВНИТЕЛЬНОМ АСПЕКТЕ - Курбонов Дониѐрбек Кахрамонович (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article is devoted to the comparative analysis of love lyrics in Western and Eastern poetic traditions. Using the example of William Shakespeare's sonnet 66 and Alisher Navoi's ghazal, which begins with the words "Kunglum kushi balo kafasida giriftor...", the article examines the common features and differences in the depiction of love, poetics and philosophical subtext of the works. The specificity of the reflection of the theme of love in the context of Renaissance humanism and the spiritual and philosophical tradition of the East is revealed.